Occurrence of OsHV-1 in Crassostrea gigas Cultured in Ireland during an Exceptionally Warm Summer. Selection of Less Susceptible Oysters - Prado-Alvarez, Maria; Darmody, Grainne; Hutton, Stephen; O'Reilly, Amy; Lynch, Sharon A.; Culloty, Sarah C. (Frontiers in Physiology, 2016)
The occurrence of OsHV-1, a herpes virus causing mass mortality in the Pacific oyster Crassostrea gigas was investigated with the aim to select individuals with different susceptibility to the infection. Naïve spat transferred to infected areas and juveniles currently being grown at those sites were analyzed using molecular and histology approaches. The survey period distinguishes itself by very warm temperatures reaching up to 3.5ºC above the average. The virus was not detected in the virus free area although a spread of the disease could be expected due to high temperatures. Overall mortality, prevalence of infection and viral load was higher in spat confirming the higher susceptibility in early life stages. OsHV-1 and oyster mortality were detected in naïve spat after 15 days of cohabitation with infected animals. Although infection was associated with mortality in spat, the high seawater temperatures could also be the direct cause of mortality at the warmest site. One stock of juveniles suffered an event of abnormal mortality that was significantly associated with OsHV-1 infection. Those animals were infected with a previously undescribed microvariant whereas the other stocks were infected with OsHV-1 µVar. Cell lesions due to the infection were observed by histology and true infections were corroborated by in situ hybridization. Survivors from the natural outbreak were exposed to OsHV-1 µVar by intramuscular injection and were compared to naïve animals. The survival rate in previously exposed animals was significantly higher than in naïve oysters. Results derived from this study allowed the selection of animals that might possess interesting characteristics for future analysis on OsHV-1 resistance.